Model Manajemen Akuakultur Air Payau Berkelanjutan: Sebuah Tinjauan Literatur - Sucipto Sucipto (Lembaga Teewan Journal Solutions, 2026)
Brackish water aquaculture plays a strategic role in supporting food security, improving economic value, and enhancing seafood export competitiveness. Despite extensive studies on individual aspects of aquaculture management, comprehensive reviews integrating technical, environmental, economic, and managerial dimensions remain limited. This study aims to develop an integrated management model for sustainable brackish water aquaculture by synthesizing evidence on pond preparation, water quality management, feeding strategies, biosecurity, disease control, harvesting, post-harvest handling, cold chain management, business feasibility, and risk management. A qualitative approach was employed using a Systematic Literature Review (SLR) of scientific articles, textbooks, aquaculture standards, and relevant regulations published within the last ten years. The synthesized findings demonstrate that integrated management improves production efficiency, optimizes resource utilization, enhances product quality, strengthens business feasibility, and increases market competitiveness. Furthermore, the integration of biosecurity, cold chain management, financial feasibility analysis, and risk management provides a comprehensive framework for minimizing operational risks while supporting long-term business sustainability. This study proposes a conceptual model of sustainable brackish water aquaculture management that integrates technical, environmental, economic, and managerial components, providing a reference for developing more productive, competitive, and sustainable aquaculture systems.